LTE-indoor: a novel PHY layer design for future 5G indoor femtocell networks. (6th July 2020) - Ting, Kuo-Chang; Wu, Jung-Shyr; Tseng, Chih-Cheng
Small cell technology such as femtocell plays an important role in 5G heterogeneous network especially in the indoor environments. However, it is unreasonable that the design of the PHY layer in femtocell networks follows that of the macrocell since the channel model used in indoor environments is entirely different from that used in urban or rural areas. To boost the PHY throughput of femtocell network, LTE-indoor (LTE-I), a new PHY layer frame structure, is proposed to accommodate more symbols in a slot time as well as to adopt higher order modulations and narrower guard bands. Furthermore, through carrier aggregation (CA) techniques, the PHY layer throughput can be further booted as high as 18.2 Gbps. The proposed LTE-I frame structure also supports the ultra-reliable and low latency communications (URLLC) by making the subcarrier spacing wider to increase the symbol rate with almost no throughput loss.